Ultrashort Peptide Bioconjugates Are Exclusively Antifungal Agents and Synergize with Cyclodextrin and Amphotericin B - Arnusch, Christopher J. (American Society for Microbiology, 2012)
Many natural broad-spectrum cationic antimicrobial peptides (AMPs) possess a general mode of action that is dependent on lipophilicity and charge. Modulating the lipophilicity of AMPs by the addition of a fatty acid has been an effective strategy to increase the lytic activity and can further broaden the spectrum of AMPs. However, lipophilic modifications that narrow the spectrum of activity and exclusively direct peptides to fungi are less common. Here, we show that short peptide sequences can be targeted to fungi with structured lipophilic biomolecules, such as vitamin E and cholesterol. The conjugates were active against Aspergillus fumigatus, Cryptococcus neoformans, and Candida albicans but not against bacteria and were observed to cause membrane perturbation by transmission electron microscopy and in membrane permeability studies. However, for C. albicans, selected compounds were effective without the perturbation of the cell membrane, and synergism was seen with a vitamin E conjugate and amphotericin B. Moreover, in combination with β-cyclodextrin, antibacterial activity emerged in selected compounds. Biocompatibility for selected active compounds was tested in vitro and in vivo using toxicity assays on erythrocytes, macrophages, and mice. In vitro cytotoxicity experiments led to selective toxicity ratios (50% lethal concentration/MIC) of up to 64 for highly active antifungal compounds, and no in vivo murine toxicity was seen. Taken together, these results highlight the importance of the conjugated lipophilic structure and suggest that the modulation of other biologically relevant peptides with hydrophobic moieties, such as cholesterol and vitamin E, generate compounds with unique bioactivity.